ANALISIS PENGGUNAAN MEDIA VIDEO ANIMASI DALAM PERKEMBANGAN HASIL BELAJAR SISWA SEKOLAH DASAR - Khusnul Khotimah; Fahrurrozi; Uswatun Hasanah; Petrus Suhendro (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The development of the times which is also followed by technological developments certainly makes a lot of changes that occur. One of the changes that can be seen is in the field of education. The entry of technology into education can make education more interesting and fun. Evidence that the entry of technology in education can make it more interesting and fun is the existence of animated video learning media. Video animation is one of the technology-based interactive learning media. With the presence of animated videos in learning, of course, it can make the learning process more fun and not boring so that it will make student learning outcomes develop well. This research is based on a literature review conducted to determine the use of animated video media in the development of learning outcomes of elementary school students. This research uses the literature review method as many as 5 articles. Based on the results of data analysis and discussion of 5 articles in the literature review, it can be concluded that the use of animated videos can improve the development of learning outcomes of primary school students and is also feasible to use in learning activities in primary schools. Keywords: Technology, Video Animation, Learning Outcomes